Konstitusionalitas dan Legalitas Norma dalam Pengujian Undang-Undang Terhadap Undang-Undang Dasar 1945 - Ali, Mohammad Mahrus (Mahkamah Konstitusi Republik Indonesia, 2015)
The Constitutionality of norms are inseparable with the model of judicial review of laws against the 1945 Constitution of the Republic of Indonesia. It can be see from the reviews of abstract and concrete norms by the Constitutional Court of the Republic of Indonesia. The review of conrete norms in the decision of judicial review basically does not constitute authority of the Constitutional Court. Theoretically, norms review should be starting from abstract norms as the implications of the Constitutional Court authority. In order to review the constitutionality of laws, norms and abstract norms should be interpreted by the Constitutional Court. While concrete norms focuse more on the implementation or application of the norm itself. The application of norms cannot be separated from the legality of the norms, while constitutionality of norms is related to its coherence with with the Constitution. If the basis of norms review is the 1945 Constitution of the Republic of Indonesia then abstract norms should be the main subject matter to be reviewed. Otherwise, when concrete norms are the subject matters to be reviewed, then the implementation of the norms that have been applied in concrete cases. This research is using normative juridical method with case approach in which 15 (fifteen) verdicts of the Constitutional Court of Republic of Indonesia over the period of 2003-2013 in judicial review of laws against the 1945 Constitution are analyzed. The focus is on the ratio decidendi of the Constitutional Court judges in determining the constitutionality of norms. The result of this research shows that, the Constitutional Court, in the judicial review of laws against the 1945 Constitution of the Republic of Indonesia does not separate abstract norms and concrete norms dichotomously. In an attempt to protect the constitutional rights of citizens, the absence of legal remedies that can be further pursued by the applicant, as well as to provide legal certainty, the Constitutional Court, granted, in its decision, the review of concrete norms. Even though the Constitutional Court remains firm in satting that it is a concrete norms, the applicant’s petition is granted in part which is concerning the review the abstract norms only. Whereas, with respect to the verdict of the constitutional court that rejected the review of concrete norms, it is because the review is not on the constitutionality of norms but the application of the norms and also concerns a petition for an interlocutory decision which is irrelevant to the subject matter of the case. The review of concrete norms in a rejecting ruling is a form of prudence by the Constitutional Court in order not to prosecute the matters which constitute the authority the other judicial bodies, namely the Supreme Court and the lower courts. As for the ruling which declared a petition inadmissible, the Constitutional Court stated that the applicant has no legal standing and the Constitutional Court does not have the authority to test these norms. In the future the Constitutional Court needs to affirm the status of norms before further examining in depth the petition filed. In addition, the Constitutional Court should be conferred with the authority to hear constitutional complaint and constitutional question in order to create the harmonization of interpretation based on the Constitution.